Covid-19 Vaccine Nationalism and Vaccine Diplomacy: A New Currency in Soft Power? (The Strategic Review for Southern Africa, 2021)
This article merges and examines the following four phenomena, (1) pandemics which are predominantly a human security matter, (2) vaccines and vaccinations, which are predominantly a public health matter, (3), power which is the alpha currency in international relations and, (4), fi nally ideology. Global developments such as wars, revolutions and pandemics usually give rise to new forms of power, redrawing power confi gurations and in some cases shift ing and redrawing biographical and geographical boundaries. This article explores the rise of vaccine nationalism and how it will impede the global eff orts to curtail the devastation of the Covid-19 pandemic. I also present the Covid-19 vaccine as a new currency in soft power that, unlike hard power, is owned by an emerging vaccine oligarchy epitomised as Big Pharma. Vaccine nationalism is positioned as being counterproductive to eff orts to reduce the eff ects of the virus. This way, vaccine nationalism and vaccine diplomacy constitute new forms of and fronts for colonialism. I conclude by asserting that vaccine nationalism will result in more asymmetrical power relations in international relations as the vaccine will gradually become a new form of soft power. As a form of soft power, the vaccine will entrench and perpetuate coloniality. Vaccine nationalism and vaccine diplomacy are self-defeating, will aid those paddling eugenics and result in a new form of inequality, vaccine inequality.